Residency training programs in anesthesiology, intensive care and emergency medicine: from curriculum to practice - Claudiu Barsac; Claudiu Barsac; Alina Petrica; Alina Petrica; Diana Lungeanu; Diana Lungeanu; Adina Maria Marza; Adina Maria Marza; Ovidiu Bedreag; Ovidiu Bedreag; Marius Papurica; Marius Papurica; et al. (Frontiers in Medicine, 2024)
Residency programs in anesthesiology and intensive care (AIC), and emergency medicine (EM) continually evolve to ensure well-prepared trainees for these critical fields of healthcare. The objective of this study was to collect comprehensive feed-back from AIC and EM residents, comprising opinions and attitudes on: curriculum and structure of the residency program; scope of training environment, opportunities and complexity; training guidance and mentorship; teaching approach. An anonymous online cross-sectional survey was conducted among AIC and EM trainees during December 2023–January 2024 and June 2023–July 2023, respectively. Two hundred and thirty-five answers were collected: 137 (73/64 female/male) and 98 (55/43 female/male) respondents from the AIC and EM programs, respectively. Overall feed-back was equivalent for both residency programs, with differences related to the distinct characteristics of each medical specialty. The main issues identified across the programs were the need to improve and diversify the teaching approaches, with trainees' strong desire for more professional guidance, mentoring, and constant feed-back. The findings would inform decision-making beyond current residency programs in these critical care specialties, highlighting the need to design solutions for interactive and highly immersive educational experiences, such as simulation, augmented reality or virtual reality.